Understanding the tale (2019)
In current education, you cannot continue doing the same tasks and still, pretend to obtain different results; Therefore, it is the teacher’s responsibility to make a self-criticism of their pedagogical work, to improve it. Bearing this in mind, this research article briefly describes the intervention, whose objective is to improve the comprehension processes of the students of the Boyacá School in Duitama Colombia, through the implementation and creation of the stories as a didactic tool. To achieve this, it was necessary first to investigate similar works, together with the appropriate theories that support it, followed by the Educational Research Action phases, obtaining significant results in terms of reading comprehension; For example, students in the process of literacy can already explain with their words, which becomes more evident at the time the student writes, with the intention of being understood by others.